Scoping the potentials and pitfalls of rural tourism policies: a constructivist perspective - Siow, May Ling; Ramachandran, Sridar; Nair, Vikneswaran (2012)
The effectiveness of policies has always been debated worldwide. In a broad perspective, there are two main types of policies, the preventive and the punitive. While some policies take a certain type, there is no conclusive evidence to support their effectiveness. The potentials and pitfalls of policies largely lie in the level of policy-making, where the analysis studied in how policy makers define problems and embed them in public policies. These include the gap in the knowledge of the nature and the extent of the problem between what is assumed to be correct by policy makers and the real nature of the situation, the level of awareness of the policies between its stakeholders, the level of acceptance and belongingness towards these policies and the level of implementation and execution of the policies. All these aspects can be summarised by the lack of interaction between policy makers and the stakeholders, which happen in most cases due to the top-down adoption in policy-making strategies. The policies in Malaysia to retain its original setting of its rural tourist destinations are widely available. The state and federal lawmakers have enacted a range of laws and policies intended to mitigate the societal and environmental risks presented by tourists. However, a similar observation of the problems in public policy is seen in the Malaysian rural tourism context, where the lack of interaction between policy makers and its stakeholders, and the flaw in the system have led to the lack of these policies being intertwined with each other. Therefore, a multi-layered adoption should be used to encourage actors` participation and interaction. The purpose of this paper is to scope the potentials and pitfalls of rural tourism policies from a constructivist perspective. The model employed to assist this study is the actor-network theory approach, where the problem is addressed using constructivism as a theoretical lens. This approach uses a qualitative design to enable the exploration of the current policy structure and the perception of the stakeholders.